Effect of arotinolol on chronic heart failure: A systematic review and meta-analysis of randomized controlled trials - Huang, Pingping; Song, Qingya; Wang, Yifei; Wang, Anzhu; Guo, Lijun; Zhang, Hongwei; Zhang, Zhibo; Ma, Xiaochang (Frontiers in Cardiovascular Medicine, 2022)
Background: Heart failure is the end stage of all cardiovascular diseases, which brings a heavy burden to the global health network. Arotinolol, as a new type of β Receptor blocker, has a good antihypertensive effect. Many clinical trials have observed the clinical efficacy of arotinolol in the treatment of essential hypertension. However, so far, there has been no systematic evaluation on the efficacy and safety of arotinolol in the treatment of heart failure. Objective: The purpose of this review was to systematically evaluate the clinical efficacy of arotinolol in patients with heart failure. Methods: Randomized controlled trials (RCTs) of arotinolol in the treatment of heart failure were retrieved from seven databases according to the Cochrane manual, including CNKI (China National Knowledge Infrastructure), Wan fang database, VIP database, PubMed, Sinomed, EMBASE, and the Cochrane Library databases. Results: A total of 17 trials met the qualification criteria, which included 1717 patients with heart failure. Most trials had uncertain risks in terms of random sequence generation, allocation hiding, patient loss, and result evaluation. Meta analysis showed that arotinolol significantly improved the treatment efficiency( p = 0.00), left ventricular ejection fraction (LVEF)( p = 0.00), cardiac index( p = 0.03), stroke volume (SV) ( p = 0.00), lower brain natriuretic peptide (BNP) ( p = 0.00), left ventricular end diastolic volume (LVEDV) ( p = 0.015). Conclusion: Arotinolol can safely and effectively improve the effective rate of patients with heart failure, increase LVEF, increase CI and SV, and reduce BNP and LVEDV. However, because of the low overall quality of the included randomized controlled trials, these findings need to be considered carefully. More high-quality randomized controlled trials are needed for further verification, to provide a more scientific basis for the safety and effectiveness of arotinolol in the clinical treatment of heart failure.